Low-Volatility Anomaly and Limits to Arbitrage : Empirical Study of Helsinki Stock Exchange - Häkkinen, Tuomas (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
This study discusses about a stock market anomaly called low-volatility anomaly or volatility-anomaly. The anomaly contradicts strongly with one of the most fundamental statements of finance by stating that the relation between risk and return could be flat or even negative. Traditional finance relies heavily on the positive relation between risk and return and the idea about investors having to bear higher risk if they want higher return is intuitively pleasing. However, the low-volatility anomaly suggests that in reality stocks with low risk have produced better returns than the ones with high risk, at least on risk-adjusted basis. If this is the case, the relation between risk and return is not similar to the one proposed by the most used financial models, like the Capital Asset Pricing Model (CAPM). The existence of low-volatility anomaly is analyzed in the Finnish stock markets through the stocks listed on the Helsinki Stock Exchange between the years 2000 to 2016. The analysis consists two parts which analyze the returns produced by investment strategy based on the anomaly but also are the returns differing drastically from the ones proposed by the CAPM. First part is the analysis about how the portfolios constructed by sorting stocks by their risk have fared through the years. The second part is the statistical analysis about the portfolios which answers the question have the portfolios produced abnormal positive returns over the CAPM with statistical significance. Furthermore, the statistical analysis also analyzes the liquidity associated with the risk-portfolios and tries to answer the question could the anomaly possibly be affected by the liquidity of the stocks. Results show that the low-volatility anomaly in the simplest way analyzed is present in the Finnish stock markets but the existence becomes questionable when risk measure changes from volatility to beta and liquidity is included through few criteria to the analysis. The performance of the portfolio consisting the stocks with low risk is far better than the one consisting high-risk stocks, which do produce the worst returns. However, the other risk-portfolios in some cases produce better returns than the lowest risk one and this further blur the picture about the anomaly. It can be stated that to some sense the low-volatility anomaly exists in the markets but when the scenario is made more realistic through the liquidity aspect as well as using the more complete risk measure of beta, the anomaly weakens radically, and cannot be distinctly observed let alone financially exploited.